TUTOR SUPPORT OF EDUCATIONAL EVENTS WITHIN THE SYSTEM FOR TEACHER FURTHER TRAINING - Svetlana V. Dudchik (Высшее образование в России)
The article presents a technology of tutor support of participants in the educational events within the system for teacher further training. Tutor support is understood as a tutor's purposeful activity facilitating the maximum entry of a teacher into the context of a modern educational practice. This activity promotes his (her) formation as a subject of professional development, and fosters the development of his (her) individual motives and values. Subjectivity of a participant of educational event is manifested in the ability to become a strategist of his (her) professional activities, to set and adjust personal goals, to realize the reasons to construct his (her) own actions and to assess their compliance with what was intended, to plan individual professional development, and to communicate effectively with colleagues.